A Research on Supply Chain Security in Malaysia - Ching Eng Leong (International Journal of Supply Chain Management, 2014)
Abstract Transportation is an important supply chain driver because products are rarely produced and consumed in the same location and industry is very dependent on the transportation to transfer the products. In todays economy, every organization is working on reducing its bottom line to get its profits up, as top line growth is almost non-existent. In logistics business, one area that can add to your organizations profitability but which is often overlooked is prevention of cargo theft. The need for cargo security is critical to assist the transportation industry in combating the serious increases in cargo crime. Cargo security is not an isolated event; security has to be applied across the value chain, across borders, (countries, departments, competitors, customers and transportation modes) and integrate an ongoing awareness in every single point of interaction with the goods. The term, cargo theft represents any stealing from premises or hijacking of cargo moving by trucks, rail cars or ships from the point of origin to the destination. It is considered cargo theft if it is stolen at any point between origin, destination and in between. Many companies normally do not report such crimes for several reasons. The security of cargo in the supply chain has become one of the major global security concerns given its recognized vulnerabilities which make cargo possibly the easiest target for criminals. Any supply chains success is closely linked to the appropriate use of a secured and safe transportation. Many companies have not yet invested in improving security beyond the minimum level due to difficulty in justifying security investments. Companies may not yet see the benefits of enhanced security or may be unable to make an adequate business case for security implementation. However, supply chain security management is not a black hole and it is believe that secured supply chains do provide a return on investment for transportation and logistics companies.